2022
DOI: 10.3390/antiox11030463
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vitamin C Deficiency and Cognitive Impairment in Older Hospitalised Patients: A Cross-Sectional Study

Abstract: Vitamin C is a powerful antioxidant and facilitates neurotransmission. This study explored association between vitamin C deficiency and cognitive impairment in older hospitalised patients. This prospective study recruited 160 patients ≥ 75 years admitted under a Geriatric Unit in Australia. Cognitive assessment was performed by use of the Mini-Mental-State-Examination (MMSE) and patients with MMSE scores <24 were classified as cognitively-impaired. Fasting plasma vitamin C levels were determined using high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Increased DNA, proteins, and lipids may be produced by free radical generation by the Fenton reaction, primarily powered by redox-active Fe 2+ and Cu 2+ . Therefore, in neurodegenerative disorders such as AD, dysregulation of biometals leads to an increase in oxidative stress, which is why metal chelators could have a role in breaking AD development [ 50 , 51 ].…”
Section: Etiology and Pathophysiology Of Admentioning
confidence: 99%
“…Increased DNA, proteins, and lipids may be produced by free radical generation by the Fenton reaction, primarily powered by redox-active Fe 2+ and Cu 2+ . Therefore, in neurodegenerative disorders such as AD, dysregulation of biometals leads to an increase in oxidative stress, which is why metal chelators could have a role in breaking AD development [ 50 , 51 ].…”
Section: Etiology and Pathophysiology Of Admentioning
confidence: 99%
“…Most animals produce relatively high levels of ascorbic acid from glucose in the liver via the glucuronic acid pathway ( Figure 5 ) [ 55 , 56 , 57 , 58 ]. Humans are unable to synthesize vitamin C and must ingest this vitamin [ 59 , 60 ].…”
Section: Biochemistry Of Antioxidants and Their Mode Of Actionmentioning
confidence: 99%
“…Several studies have explored the associations between vitamin C and physical and mental well-being; its deficiencies may increase the risk of severe conditions such as cancer, heart disease, and diabetes [131][132][133]. Research has also found links between vitamin C deficiency and attention, concentration, executive function, memory, linguistic and conceptual thinking [134][135][136]. Low levels of vitamin C can negatively affect mood, potentially leading to depression and cognitive impairment [137], in other words, higher levels of vitamin C are correlated with improved mood and reduced depression and confusion [134].…”
Section: Vitamin C Vitamin E and Other Antioxidantsmentioning
confidence: 99%
“…Research has also found links between vitamin C deficiency and attention, concentration, executive function, memory, linguistic and conceptual thinking [134][135][136]. Low levels of vitamin C can negatively affect mood, potentially leading to depression and cognitive impairment [137], in other words, higher levels of vitamin C are correlated with improved mood and reduced depression and confusion [134]. A meta-analysis has described how vitamin C supplementation can enhance the mood in individuals with depression [138].…”
Section: Vitamin C Vitamin E and Other Antioxidantsmentioning
confidence: 99%